Measuring financial integration in new EU member states - Markus Baltzer; Lorenzo Cappiello; Roberto A. De Santis; Simone Manganelli (European Central Bank (ECB), 2008)
The study considers three broad categories of financial integration measures: (i) price-based, which capture discrepancies in asset prices across different national mar kets; (ii) news-based, which analyse the impact that common factors have on the return process of an asset; (iii) quantity-based, which aim at quantifying the effects of frictions on the demand for and supply of securities. This paper finds that financial markets in the new EU Member States (plus Cyprus, Malta and Slovenia) are significantly less integrated than those of the euro area. Nevertheless, there is strong evidence that the process of integration is well under way and has accelerated since accession to the EU.
Keywords: 330; Finanzmarkt; Integration; EU-Mitgliedschaft; EU-Staaten; EU-Mitgliedschaft